Crispin : at the edge of the world / 2. - Avi, 1937- (Hyperion Books for Children, 2006)
Branded as traitors by the king's authorities, Crispin and his guardian, Bear, flee to coastal towns in fourteenth-century England, where they perform a musical juggling act and bond as a family after befriending a disfigured girl.